Pregunta
Suppose that the functions \( q \) and \( r \) are defined as follows. \[ \begin{array}{l}q(x)=-2 x \\ r(x)=2 x^{2}-1 \\ \text { Find the following. } \\ (r \circ q)(-1)=7 \\ (q \circ r)(-1)=\square\end{array} \]
Ask by Bond Goodwin. in the United States
Feb 03,2025
Solución de tutoría real
Respuesta verificada por el tutor
Responder
\((q \circ r)(-1) = -2\)
Solución
To find \((q \circ r)(-1)\), we first need to evaluate \(r(-1)\) and then apply the function \(q\) to the result.
1. **Calculate \(r(-1)\):**
\[
r(x) = 2x^2 - 1
\]
\[
r(-1) = 2(-1)^2 - 1 = 2(1) - 1 = 2 - 1 = 1
\]
2. **Apply \(q\) to the result of \(r(-1)\):**
\[
q(x) = -2x
\]
\[
q(r(-1)) = q(1) = -2(1) = -2
\]
Therefore, \((q \circ r)(-1) = -2\).
**Answer:** \(-2\)
Revisado y aprobado por el equipo de tutoría de UpStudy
Como
error msg
Explicar
Simplifique esta solución
Mind Expander
To find \((q \circ r)(-1)\), we need to first compute \(r(-1)\) and then apply the function \(q\) to the result. 1. Calculate \(r(-1)\): \[ r(-1) = 2(-1)^2 - 1 = 2(1) - 1 = 2 - 1 = 1 \] 2. Now, use the result from \(r(-1)\) to find \(q(r(-1)) = q(1)\): \[ q(1) = -2(1) = -2 \] Thus, \((q \circ r)(-1) = -2\).
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde
Hazte Premium